A survey of HDCO and D2CO towards Class 0/I proto-brown dwarfs. Issue 3 (11th June 2022) - Riaz, B; Thi, W-F
ABSTRACT: Deuterium fractionation can constrain the physical and chemical conditions at the early stage of brown dwarf formation. We present IRAM 30-m observations over a wide frequency range of 213–279 GHz of singly and doubly deuterated species of formaldehyde (HDCO and D2 CO) towards Class 0/I proto-brown dwarfs (proto-BDs). Multiple low-excitation HDCO and D2 CO transition lines with upper energy level ≤40 K are detected. The D2 CO/HDCO, HDCO/H2 CO, and D2 CO/H2 CO abundance ratios range between 0.01 and 2.5 for the proto-BDs, similar to the range seen in low-mass protostars. The highest ratios of D2 CO/HDCO ∼1.3–2.5 are measured for two Stage 0 proto-BDs. These objects could possess a warm corino, similar to the few hot corino cases reported among Class 0 protostars. The mean D2 CO/HDCO, D2 CO/H2 CO, and HDCO/H2 CO ratios for the proto-BDs are comparatively higher than the range predicted by the current gas-grain chemical models, indicating that HDCO and D2 CO are formed via grain surface reactions in the dense and cold interiors of the proto-BDs at an early formation stage.